Making Future of Bali: a leading destination for Medical Tourism - Ida Bagus Amertha Putra Manuaba (Bali Tourism Board, 2021)
Bali Provincial Government has taken several steps to diversify the Balinese economy sectors. Medical Tourism became a proposal in line with the Indonesian government’s tourism sector development plan for the past five years. They continue to improve the domestic health industry. Not wanting to depend on imports continuously, Authorities since 2020 has committed to making improvements in the governance of state-owned and private companies, especially in the pharmaceutical, medical devices, and health facilities. The construction of an International Hospital (RSI) in Sanur, Bali, in collaboration with the Mayo Clinic Cancer Hospital in the United States, has been seriously monitored to create leading health service standards in Indonesia. Later, the community can use Bali RSI to carry out various medical treatments. Therefore, in the future, health tourism can be properly established. Another image would be emerging: Bali, a top-class holiday destination that serves as a sanctuary to rejuvenate one’s health.